Intelligent Decision Technologies 2019. Proceedings of the 11th KES International Conference on Intelligent Decision Technologies (KES-IDT 2019) /: Proceedings of the 11th KES International Conference on Intelligent Decision Technologies (KES-IDT 2019). Volume 1 : ([2020]) - KES International., Symposium on Intelligent Decision Technologies, (11th) 2019 (Malta)
No abstract available